Mediterranean Fruit Fly, Ceratitis capitata (Wiedemann) (Insecta: Diptera: Tephritidae) - Michael C. Thomas; John B. Heppner; Robert E. Woodruff; Howard V. Weems, Jr.; Gary J. Steck; Thomas R. Fasulo (EDIS)
The Mediterranean fruit fly, Ceratitis capitata (Wiedemann), is one of the world's most destructive fruit pests. The species originated in sub-Saharan Africa and is not known to be established in the United States. When it has been detected in Florida and California, especially in recent years, each infestation necessitated intensive and massive eradication and detection procedures so that the pest did not become established. This document is EENY-214 (originally published as DPI Entomology Circulars 4, 230 and 273), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2001. Revised: September 2001.